A facile naphthalene-based fluorescent 'turn-on' chemodosimeter for palladium ions in aqueous solution. Issue 10 (9th March 2016) - Chen, Yu; Chen, Bo; Luo, Daijun; Cai, Yiyu; Wei, Yaning; Han, Yifeng
Graphical abstract: Abstract: A novel and simple depropargylation-triggered spontaneous cyclization reaction based fluorescent turn-on chemodosimeter for the detection of Pd 2+ has been reasonably designed and developed. Based on the specific reactivity of palladium ion-promoted hydrolysis reaction, the probe exhibited a high selectivity and sensitivity for Pd 2+ with a low detection limit (53 nM, 5.7 μg/L) under physiological conditions in neutral PBS (only containing 1% organic cosolvent) without any additional reagents.